Літологічний склад, колекторські властивості та газоносність пісковиків кам’яновугільного віку Львівсько-Волинського вугільного басейну (поле шахти Тяглівська № 1) - Бучинська, І. (Геологія і геохімія горючих копалин, 2010)
Вмісні породи мають велике значення для формування газоносності вугленосних товщ, нагромадження і міграції метану. Досліджено пісковики серпуховського ярусу нижнього карбону та башкирського ярусу середнього карбону Тяглівського родовища Львівсько-Волинського кам’яновугільного басейну. Побудовано схеми газоносності цих пісковиків. У деяких стратиграфічних інтервалах газоносність є досить високою . Газоносність пісковиків зменшується з глибиною, що пов’язано з погіршенням колекторських властивостей порід, зумовленим ступенем постседиментаційних змін, структурно-тектонічними і гідрогеологічними умовами залягання. Дегазація пісковиків безперервна і нерівномірна, що пояснюється не лише їхньою низькою газопроникністю, але й ускладненням моноклінальних схилів пологими куполоподібними антиклінальними підняттями, куди з великих площ можуть надходити гази шляхом вертикальної та латеральної міграції. Studies of the gas potential of the coal-bearing series are impossible without studies of collector properties or rocks containing the coal seams. Their gas potential is not large and depends upon the lithological composition of the cover and basement, tectonic structure of the region. In connection with the great volume occupying by rocks in the section of series, the amount of natural gases in them may be sufficient. The possibility of the gas accumulation in mountain rocks is determined by the conditions of their sedimentation, the rate of post-sedimentary changes, structural-tectonic and hydrogeological conditions. Accumulation of gases in sandstones and aleurolites of early stages of coal metamorphism may occur only in the conditions of lithological, stratigrapfic, structural-tectonic and other kind of tops. Maps of gas potential were compiled for sandstones of the Tyagliv field. On the whole, one can state that for some stratigraphic intervals the gas potential is rather high. Decrease in the gas potential of enclosing series is observed with the depth. This is connected with change of collector properties of rocks for the worse that is defined by the degree of their postsedimentary changes, structural-tectonic and hydrogeological conditions of occurrence. In the maps it is clear that the process of degassing of sandstones runs continuously and occurs very uneven. This is connected not only with the low gas permeability of sandstones, but with complication of monoclinal slopes by gently sloping dome-like anticlinal bends where gases from rather large areas may be collected as a result of lateral migration.